2016
DOI: 10.1007/s10591-015-9366-2
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and Family Therapy Students’ Views on Including Weight Bias Training into Their Clinical Programs

Abstract: Discussions about diversity rarely focus on overweight, obesity, and bias about body size (i.e., weight bias). These discussions allow students to develop selfawareness about how their biases can affect their clinical work, as well as the challenges and subsequent bias clients may face in their everyday lives and from clinical providers. One consequence of the rising prevalence of overweight and obesity in the United States is the increase in the level of weight bias and discrimination towards individuals who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This study also highlights and confirms other findings that reflect that the role of bias merits consideration when developing training programs, some of which may be shaped by personal experiences. These findings remain consistent with previous research that indicated that a lack of clinical training and bias towards persons experiencing weight-related issues, such as obesity [7], can serve to influence how therapists interact with obese patients in their future work. While revamping the training process [6] prefaces the idea that instructors in the MFT programs must ensure that student clinicians receive the necessary tools to provide sensitive treatment to clients impacted by obesity, it is also pertinent that future research focus not only on biases about clients, but therapists' own personal perceptions and experiences regarding weight as well.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This study also highlights and confirms other findings that reflect that the role of bias merits consideration when developing training programs, some of which may be shaped by personal experiences. These findings remain consistent with previous research that indicated that a lack of clinical training and bias towards persons experiencing weight-related issues, such as obesity [7], can serve to influence how therapists interact with obese patients in their future work. While revamping the training process [6] prefaces the idea that instructors in the MFT programs must ensure that student clinicians receive the necessary tools to provide sensitive treatment to clients impacted by obesity, it is also pertinent that future research focus not only on biases about clients, but therapists' own personal perceptions and experiences regarding weight as well.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies [7], some participants in the study struggled with the notion of what their roles entail in working with obese clients. This study also highlights and confirms other findings that reflect that the role of bias merits consideration when developing training programs, some of which may be shaped by personal experiences.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations